Applications of Domino Transformations in Organic Synthesis. Band 1 und 2. Science of Synthesis Workbench Edition. Herausgegeben von Scott A. Snyder. (6th October 2016) - Menche, Dirk
Abstract : Thieme, Stuttgart 2016. 1260 S., Broschur, 449.00 €.—ISBN 978‐3132401631